Behavior of reinforced concrete sandwiched panels (RCSPs) under blast load. (15th February 2019) - Abbas, Asim; Adil, Mohammad; Ahmad, Naveed; Ahmad, Izaz
Highlights: Experimental blast load testing of reinforced concrete sandwiched panels (RCSPs) in field conditions. Damage behavior of RCSPs under blast loading. Fragility curves for RCSP walls, correlating damage with charge weight and distance of explosives. Abstract: This paper presents an experimental investigation carried out to understand the behavior of reinforced concrete sandwiched panels (RCSPs) under blast load. An RCSP is composed of an EPS (Expanded Polystyrene) foam core, which is surrounded by spray-on reinforced concrete skins (like ferrocement overlay) on both sides. For this purpose blast load test on four free-standing RCSPs in 17 blast case scenarios were conducted and the physical behavior was analyzed through high quality visuals and fragility curves were developed. The fragility curve interprets the relationship between damage intensity with charge size and scaled of distance. On the basis of results it is concluded that RCSP panel has greater capability of absorbing and dissipating energy generated by blast, and stable against fragmentation as compared to other conventional building systems used in Pakistan. Based on the assessment RCSPs walls/panels are strongly recommended for protective barrier installed in the vicinity of critical infrastructure against blast loading.